2018
DOI: 10.1038/s41395-018-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Open: Effects of NGM282, an FGF19 variant, on colonic transit and bowel function in functional constipation: a randomized phase 2 trial

Abstract: NGM282 significantly impacts GE and colonic transit, consistent with the observed clinical symptoms. The specific mechanism of prokinetic activity requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Nonetheless, because bile acids stimulate colonic secretion of water and high-amplitude-propagated contractions 23 , 24 , it is hypothesized that a paucity of colonic bile acids may cause constipation. Indeed, the corollary is also true: excess bile acid administered orally 24 or modification of the enterohepatic recycling pathway 25 can exert a laxative effect.…”
Section: Advances In Understanding the Molecular Pathophysiology Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, because bile acids stimulate colonic secretion of water and high-amplitude-propagated contractions 23 , 24 , it is hypothesized that a paucity of colonic bile acids may cause constipation. Indeed, the corollary is also true: excess bile acid administered orally 24 or modification of the enterohepatic recycling pathway 25 can exert a laxative effect.…”
Section: Advances In Understanding the Molecular Pathophysiology Of Cmentioning
confidence: 99%
“…In patients with functional constipation, the fibroblast growth factor 19 analog NGM282 accelerated gastric and colonic transit, resulting in an increased number of bowel movements, looser stool form, and increased ease of stool passage 25 . The rationale for this study was the observation that NGM282 induced diarrhea in phase 2 trials relating to type 2 diabetes, primary biliary cholangitis, and non-alcoholic steatohepatitis.…”
Section: Development Of Novel Therapeutic Agents For the Treatment Ofmentioning
confidence: 99%
“…FGF19 primarily targets the liver, which expresses both components (FGFR4 and β‐klotho) required for FGF19 signaling . (Pre)clinical studies revealed a myriad of functions of FGF19/Fgf15 including regulation of major metabolic pathways (e.g., energy, carbohydrate and lipid metabolism, bile salt and protein synthesis) and functional processes such as gallbladder relaxation, skeletal muscle mass homeostasis, and GI motility . Considering the beneficial metabolic effects, FGF19 administration is evaluated as treatment of chronic liver diseases .…”
mentioning
confidence: 99%
“…Although there is no evidence for any genetic mutation of FGF19 gene that may be involved in human metabolic diseases, its reduced synthesis and blood levels are suggestive of a causative factor of chronic bile acid diarrhea [80,81] and certain metabolic disorders, such as metabolic syndrome, nonalcoholic fatty liver disease (NAFLD), and insulin resistance. Experimentally, the Fig.…”
Section: Fgf19 Metabolic Axismentioning
confidence: 99%
“…It markedly reduced liver fat content but with significant side effects [70]. In a phase 2 trial in patients with type 2 diabetes and chronic idiopathic constipation, NGM282 significantly improved bowel function by accelerating gastric emptying and colonic transit [81]. Furthermore, NGM282 was further tested in mouse models and human patients with cholestasis and primary biliary cholangitis, showing efficacy in significantly reducing bile acid levels and improving hepatic inflammatory injury and fibrosis [84,88,89].…”
Section: Fgf19 Metabolic Axismentioning
confidence: 99%